FORMULASI STRATEGI PEMASARAN MENGGUNAKAN ANALISA QSPM (STUDI PADA SUOKLAT CAFE DI SURABAYA) - Iis Rohmawati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
The aim of this research is: (1) Identifying and analyzing internal and external environment of the company that influence the marketing strategy of Suoklat Cafe. (2) Formulating the alternative marketing strategy of Suoklat Cafe that is obtained from the analysis result. (3) Formulating and setting the strategy formula that is most suitable to improve Suoklat Cafe. The data collection is taken from April to August 2016 in Suoklat Cafe located in Surabaya. Internal Analysis (IFE) results the primary factor focusing on chocolate products with the score 0,172. Meanwhile, the main weakness from this business is the less appropriate management implementation process scoring 0, 117. When the two internal factors are combined, the average total score is 2, 635. External Analysis (EFE) results main opportunity that can be used by Suoklat Cafe in order to face the competition; hanging out culture in Cafe in Surabaya by 0,216. The main threat that can be obtained from the calculation shows through the strong factor of bargaining high supplier, scoring 0, 212. Based on the two external factors that is obtained, the average score is 2, 916. IE Analysis in Suoklat Cafe positions it in quadrant V, known as maintaining and preserving strategy. SWOT analysis results strategies that can be applied: (1) Maintaining the price, increasing the variation and the product quality in order to enchance the loyality and consumers' satisfactions, (2) Expanding the market share, (3) Maintaining and improving the service quality towards the consumers (4) improving the internal managemeny of the company (5) streghten the capital through cooperations with the media, the investors, and the governmeny agencies (6) analyzing the competitors to find out tje advantages and the disadvantages, and also streghten the consumer-supplier relationship to help increase the loyality (7) Improving the effeciency and effectiveness of the employee's work, expanding the location of the parking area or cooperating with local authorities, also increasing the technology. The QSPM processing results the production of main prior strategy that sets market share expansion to face the competition with TAS 6, 422.